STUDY OF 1-D (ONE DIMENSIONAL) AND 2-D (TWO DIMENSIONAL) FLOOD MODELLING USING HEC-RAS 5.0.7 - Mashuri; M Gilang Indra Mardika; Hayyu Sariyah (Jurnal Infrastruktur, 2023)
The Way Sulan River lies in Way Sulan's sub-watershed and often causes flooding during the rainy season. The disaster brought losses and damages as it caused inundation in the paddy fields and tore down the embankment and the bridge in the Way Sulan River. Flood mitigation is required to reduce the aftermath that may occur in the future. Flood modeling is a basic step of flood control to identify areas that are vulnerable of flooding. In this study, the flood modeling is carried out using HEC-RAS 5.0.7, performed by the 1-D and 2-D unsteady flow analysis. The flow hydrograph is calculated using the SCS SUH method and then used as an input on the HEC-RAS model. The calculation shows that the maximum design discharge for a 25-year return period is 124.416 m3/s. The flood modeling outputs show that the 2-D model provides a higher variation of the velocity and maximum water surface elevation than the 1-D model. The average ratio of the maximum velocity of the 1-D and 2-D models is 4.19%, while the average ratio of the maximum water surface elevation is only 1%. In the 1-D model, the highest velocity is 0.87 m/s at River Station 4580 (middle area) and the highest maximum water surface elevation is 8.77 m at River Station 6980 (upstream). On the other hand, the two-dimensional model gives the highest velocity at River Station 4580 (middle area) is 0.88 m/s and the highest maximum water surface elevation is at the River Station 8960 (upstream) which is 8.85 m. Based on the 2-D modelling, it is known that the potential flooded land-use area is 79.53 Ha of paddy fields, 6.83 Ha of farmland, and 4.59 Ha of the plantation.